Targeting CXCL8 signaling sensitizes HNSCC to anlotinib by reducing tumor-associated macrophage-derived CLU - Xin Hu; Yikang Ji; Mi Zhang; Zhihui Li; Xinhua Pan; Zhen Zhang; Xu Wang (Journal of Experimental & Clinical Cancer Research)
Abstract Background Although nutrition-starvation therapy for malignancies such as HNSCC is highly desirable, the clinical outcomes remain disappointing. Understanding the spatial heterogeneity of glucose deficiency can reveal the molecular mechanisms regulating cancer metabolism and identify therapeutic targets to improve effective nutrient-starvation therapies. Methods Multiple omics data from RNA-seq, proteomics and spatial transcriptome analyses of HNSCC samples were integrated to analyze the spatial heterogeneity of glucose deficiency. In vivo and in vitro CXCL8 and CLU expression levels in tumor cells were determined using qPCR, immunohistochemistry and ELISA. The ability of CLU from TAMs to respond to tumor-derived CXCL8 was assessed using RNA sequencing, siRNA silencing, immunofluorescence and CCK-8 assays. A mouse subcutaneous xenograft model was used to assess the outcomes of nutrition-starvation therapy combined with blockade of CXCL8 signaling. Results A set of genes that was significantly upregulated in HNSCC under conditions of glucose deficiency was identified using integrating multiple omics data analyses. The upregulated gene set was used to determine the glucose-deficient area according to transcriptome data of HNSCC, and CXCL8 was one of the most highly upregulated genes. The levels of both CXCL8 mRNA and its protein IL-8 in cancer cells under conditions of glucose deficiency were increased in an NF-κB-dependent manner. Supplementary IL-8 stimulated TAMs to synthesize CLU, and CLU counteracted oxidative stress in HNSCC cells under conditions of glucose deficiency. Moreover, pharmacological blockade of CXCL8 signaling (reparixin) sensitized HNSCC cells to nutrient-starvation therapy (anlotinib) in two xenograft models. Conclusion Our results provide novel evidence of a feedback loop between cancer cells and TAMs in glucose-deficient regions. HNSCC-derived CXCL8 favors endogenous antioxidative processes and confers therapeutic resistance to nutrient-starvation therapies in HNSCC. Graphical Abstract